SISTEM INFORMASI PEMESANAN JASA RENTAL KENDARAAN DAN PAKET WISATA SABILA TRANSPORT - , ARIE SADEWA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sabila Transport Company is a company engaged in the vehicle rental services and tour packages . This company is one of the leading companies in Yogyakarta , but the handling of the order and how to order the data is still simple to use way . Data processing is less tidy can cause errors in each order will be processed by the company . Based on these problems , need to build a system capable of handling the booking process until the data processing orders cent to become more optimal . The system is capable of handling the booking process , data processing orders as well as rental vehicles travel packages Sabila Transport . Booking Information Systems Vehicle Rental Services and Tour Packages built using Codeignniter framework and MySQL database. The system can order various types of transportation and tour packages online.